Karamunting Fruit Gel as a Natural Dental Plaque Disclosing Solution - Silvia Prasetyowati; M. Ibraar Ayatullah; Sunomo Hadi (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Dental and oral health issues remain a global challenge, with rising dental caries cases, particularly in regions like Sub-Saharan Africa and Indonesia, where 57.6% of the population is affected. Among Indonesian children aged 3-9, caries and toothache are prevalent, highlighting the need for early plaque detection and targeted interventions. This study aims to evaluate the effectiveness of disclosing solution gel formulated from Karamunting fruit (Melastoma malabathricum L.) as a dental plaque identifier in children attending the Special Education School under the Surabaya Foundation for Children with Disabilities. Methods: This study utilized a quasi-experimental design using a post-test with a control group framework. A total of 24 respondents were selected through random sampling and divided into four groups. The first three groups were given Karamunting fruit gel at concentrations of 7.5%, 10%, and 12.5% respectively, while the fourth group received a chemically-based disclosing solution as the control. This design allowed for a comparative analysis of the effectiveness of the natural and chemical formulations in detecting dental plaque. Results: The result of the analysis, conducted by using Kruskal-Wallis revealed a p-value of 0.004 (<0.05) indicating a statistically significant effectiveness among Karamunting gel concentrations of 7.5%, 10%, and 12.5% when compared to chemically-based disclosing solution. These findings demonstrate that Karamunting gel is effective in identifying dental plaque, with its efficacy varying significantly according to the concentration used. Conclusion: The disclosing solution gel derived from Karamunting fruit (Melastoma malabathricum L.) showed a potential as an effective alternative for dental plaque notification.